Ozone therapy for high-grade glioma: an overview - Yanchu, Li; Rong, Pu; Rong, Cao; Li, Zhang; Xiaoyan, Yang; Feng, Wang (Frontiers in Oncology, 2023)
High-grade gliomas (grades III and IV) are highly malignant and aggressive brain tumors that present significant treatment challenges. Despite advances in surgery, chemotherapy, and radiation therapy, the prognosis for patients with glioma remains poor, with a median overall survival (mOS) range of 9–12 months. Therefore, exploring new and effective therapeutic strategies to improve glioma prognosis is of utmost importance and ozone therapy is a viable option. Ozone therapy has been used in various cancers, such as colon, breast, and lung, yielding significant results in preclinical studies and clinical trials. Only a few studies have been conducted on gliomas. Furthermore, since the metabolism of brain cells involves aerobic glycolysis, ozone therapy may improve the oxygen condition and enhance glioma radiation treatment. However, understanding the correct ozone dosage and optimal time of administration remains challenging. Herein, we hypothesize that ozone therapy should be more effective in gliomas compared to other tumors. This study provides an overview of the use of ozone therapy in high-grade glioma, including mechanisms of action, preclinical data, and clinical evidence.